PENGARUH PENDAPATAN PERKAPITA DAN TENAGA KERJA SEKTOR PERTANIAN TERHADAP PERTUMBUHAN SEKTOR PERTANIAN DI KALIMANTAN BARAT PERIODE 2010-2014 - B01110055, Imanuel (Jurnal Curvanomic, 2017)
This study entitled "Effect of Per Capita Income And Agriculture Labor Against Agricultural Sector Growth In West Kalimantan Period 2010-2014" with the aim Testing the effect of per capita income and labor to growth in the agricultural sector districts / cities in West Kalimantan.The method used in this type of research is explanatory research by using secondary data, panel data comprising data time series and cross section from 2010 to 2014. The program processed by computer using software economics views (E-views). using fixed effect method Panel Least Square (PLS).The results of the discussion concluded that based on the t-statistic capita income has no effect significantly to agricultural growth with a probability value of 0.7367 is greater than 0.05%, agricultural labor has a significant influence on the growth of the agricultural sector with a probability value 0.0022 less than 0.05%. While the f-test statistic (synchronously) can be seen from the probability value of 0.0000177 f-statistic is less than 0.05%, which means jointly capita income and agricultural labor affect the growth of the agricultural sector. Determination test showed R2 value of 0.509141 means that 50.91% variable agricultural growth can be explained by per capita income and agricultural labor.Keywords : Growth in the agricultural sector, per capita income and agricultural labor